A Bibliometric Analysis of Social Media Utilization by Political Parties in the Context of Digital Democracy - Akhmad Habibullah; Lahveenya Panchalingam; Doston Pirnazarof (Universitas Muhammadiyah Ponorogo, 2026)
The growing use of social media by political parties has reshaped the landscape of political communication and campaign strategies in the digital democracy era. This study maps the evolution of scholarly literature on the utilization of social media by political parties from 2015 to 2025. Using bibliometric analysis through VOSviewer and data from the Scopus database, 97 peer-reviewed articles were examined to identify publication trends, dominant keywords, thematic structures, and patterns of author and country collaboration. The results reveal a significant increase in publications after 2019, especially during the COVID-19 pandemic, reflecting a global shift toward digital campaigning. Key themes include social media, political communication, elections, disinformation, and populism, indicating growing scholarly attention to digital political transformation. The United Kingdom, Germany, and Spain emerged as the most productive contributors to this research field. However, the study is limited by its exclusive reliance on Scopus-indexed English-language publications, potentially overlooking non-English or regional studies, particularly from developing democracies. Future research should incorporate comparative datasets, mixed-method analyses, and deeper explorations of emerging platforms such as TikTok or Telegram to capture the evolving dynamics of algorithmic politics and audience engagement in digital democracy. Keywords: Social Media; Political Communication; Digital Campaigns; Disinformation; Political Parties;